2013
DOI: 10.1136/bjsports-2013-092826
|View full text |Cite
|
Sign up to set email alerts
|

Repeated sprint training in normobaric hypoxia

Abstract: Repeated sprint ability (RSA) is a critical success factor for intermittent sport performance. Repeated sprint training has been shown to improve RSA, we hypothesised that hypoxia would augment these training adaptations. Thirty male well-trained academy rugby union and rugby league players (18.4±1.5 years, 1.83±0.07 m, 88.1±8.9 kg) participated in this single-blind repeated sprint training study. Participants completed 12 sessions of repeated sprint training (10×6 s, 30 s recovery) over 4 weeks in either hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
101
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(119 citation statements)
references
References 39 publications
11
101
1
6
Order By: Relevance
“…In this regard, the proposed effect of RSH on RS performance was observed without prior exercise and in normoxic conditions [2][3][4][5] . Whether such effect can be extrapolated to situations including prior exhaustive exercise (such as at the end of a XC-ski or bicycle race) and hypoxic conditions remains uncertain; if confirmed, RSH could be of major relevance for athletic competitions critically determined in fatiguing conditions and/or carried out at altitude 7 .…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…In this regard, the proposed effect of RSH on RS performance was observed without prior exercise and in normoxic conditions [2][3][4][5] . Whether such effect can be extrapolated to situations including prior exhaustive exercise (such as at the end of a XC-ski or bicycle race) and hypoxic conditions remains uncertain; if confirmed, RSH could be of major relevance for athletic competitions critically determined in fatiguing conditions and/or carried out at altitude 7 .…”
Section: Introductionmentioning
confidence: 83%
“…If applying the criterion for exhaustion used herein (<70 % of the best (peak) sprint power output), the number of repeated sprints accomplished would be apparently similar following RSH vs. RSN in the above studies, which either did not use any criterion 3 or did apply the <70 % power criterion but not related to the actual best sprint power output 4 . Nevertheless, a single-blind study evaluating the effects of RSH has reported an increase in the distance covered in the Yo-Yo intermittent recovery test after 4 weeks of training in well trained rugby players 5 . Taken together, RSH does not seem to improve RS ability with regard to RSN when both a rigorous criterion for exhaustion/task failure and a double-blind design are applied.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that the subjects were never asked to perform the 25 m at maximal velocity. The feature of the present study was therefore distinguishable from that of the RSH studies (11,13).…”
Section: Methodsmentioning
confidence: 77%
“…The majority of the controlled studies that reported advantageous effects used exercise intensities equal to or higher than the second ventilatory threshold (8,31). Furthermore, some remarkable effects have been highlighted these last 2 yr after training with repeated sprint (i.e., short all-out exertions) in hypoxia (RSH) (11,13), which could be considered as a superior form of IHT. Thus, one could assume that such results could be reproduced through VHL training at high intensity, especially because the intermittent hypercapnic effect may play an additional role in the physiological adaptations leading to improved performance.…”
mentioning
confidence: 97%